A topcoat for photocured diamond scintillating coatings and a method of making the same
Patent Information
- Application Number
- CN202611231785.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-14
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2046-08-14
AI Technical Summary
[0006]针对以上问题,本发明提供一种光固化钻石火星涂层用面漆及其制备方法,用于解决目前光固化钻石火星涂层用面漆存在固化后超硬粉体易从涂层中脱落以及附着力偏差的问题
[0024](1)本发明提供的光固化钻石火星涂层用面漆,采用以金刚烷为核心骨架、分子结构中同时含有磺酸基团、有机硅链段和有机氟链段的硅氟改性磺酸型光固化树脂作为基体树脂。金刚烷的刚性笼状结构赋予树脂高硬度和良好的热稳定性;磺酸基团能够与超硬耐磨粉表面产生强极性相互作用,增强填料锚固力;有机硅链段中的硅氧键具有较高的键能和柔顺性,能够在涂层与底漆层界面处形成有效的分子链缠结和极性相互作用,提升涂层对底漆层的润湿性与附着锚固力,同时可调节树脂网络的柔韧性和交联密度,有助于吸收和分散外力冲击,降低耐磨粉颗粒在应力作用下的界面脱粘倾向;有机氟链段则因碳氟键较低的极化率和表面自由能,能够在固化过程中优先迁移至涂层表面和内部微孔界面,形成致密的低表面能屏障,有效阻隔有机溶剂分子的渗透和溶胀破坏,赋予涂层优异的耐溶剂性。
Smart Images

Figure CN122772486B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of polymer composite materials technology, specifically a topcoat for photocurable diamond Mars coating and its preparation method. Background Technology
[0002] With the increasing demands for both the decorative and durable properties of wood-based panels from modern home decoration, high-end wood product processing, and commercial space renovation industries, traditional coating systems are struggling to meet the performance requirements of high-frequency use and high-wear environments. In the field of wood-based panel surface coating technology, hardness and abrasion resistance remain core indicators for evaluating coating performance. Traditional polyurethane and nitrocellulose lacquer systems suffer from inherent defects such as low hardness (typically 1H~2H), poor abrasion resistance, long curing cycles, and high VOC emissions. While UV curing technology has brought about rapid drying and environmental benefits, existing UV coatings still face bottlenecks: the contradiction between hardness and flexibility caused by high-functionality resins; the abrasion resistance limit caused by conventional alumina and silica fillers (Mohs hardness below 9); and the insufficient adhesion of highly cross-linked coatings to porous wood substrates.
[0003] Against this technological backdrop, the industry has proposed the concept of "diamond spark coating". This coating uses diamond (Mohs hardness 10) micro powder as the core wear-resistant reinforcing phase, which not only greatly improves the scratch resistance, but also generates sparks (sparks) when the diamond particles rub violently against the abrasive during high-speed grinding and polishing, which is a direct representation of the coating's ultra-high hardness and wear resistance.
[0004] In the Diamond Mars coating system, the topcoat, as the outermost layer applied over the primer, is the "first line of defense" directly facing the harsh external environment, playing a crucial role. The topcoat directly bears the brunt of extreme mechanical forces. Everyday scratches from hard objects, high-frequency foot friction, and heavy impacts all act on the topcoat surface first. This requires the topcoat to not only possess extreme surface hardness but also for the ultra-hard powder to have extremely strong interfacial anchoring force within the resin matrix. Once the powder is impacted and detached, the wear resistance will drastically decrease. Furthermore, the topcoat is the ultimate barrier against chemical erosion. As the outermost layer, it must withstand repeated wiping and swelling from solvents such as detergents, oils, and acetone over a long period, preventing the medium from penetrating and damaging the coating network. Finally, the topcoat is the key link maintaining the integrity of the coating system. As the outermost layer, the internal stress generated by its curing shrinkage and the deformation stress generated by heat and moisture must be transferred to and released by the primer through excellent interfacial adhesion; otherwise, it is very easy to cause interlayer delamination between the topcoat and primer, leading to the failure of the entire coating system.
[0005] However, ultra-hard powders such as diamond and silicon carbide have low surface polarity and extremely poor compatibility with conventional organic resins. When the coating is subjected to impact or high-frequency friction, the powder is easily pulled out and detached from the matrix, resulting in a high "impact powdering rate." The wear resistance decreases sharply over time, making it difficult to realize the true wear resistance potential of diamond. Moreover, due to the addition of a large amount of ultra-hard powders such as diamond and silicon carbide, the adhesion of the topcoat is poor. Summary of the Invention
[0006] To address the above problems, this invention provides a topcoat for photocurable diamond Mars coating and its preparation method, which solves the problems of easy detachment of ultra-hard powder from the coating and poor adhesion in current photocurable diamond Mars coating topcoats.
[0007] To achieve the above objectives, the technical solution adopted by the present invention is as follows:
[0008] A photocurable diamond Martian coating topcoat comprises the following components in parts by weight: 50-60 parts of silicone-fluorine modified sulfonic acid photocurable resin, 11-16 parts of trifunctional acrylate monomer, 8-12 parts of difunctional acrylate monomer, 3-5 parts of monofunctional acrylate monomer, 12-16 parts of superhard wear-resistant powder, and 4-5 parts of photoinitiator; wherein the superhard wear-resistant powder is composed of diamond particles, zirconium oxide particles, and silicon carbide particles in a mass ratio of 4-5:7-9:9-12, and the average particle sizes of the diamond particles, zirconium oxide particles, and silicon carbide particles are 4-8 μm, 10-16 μm, and 10-16 μm, respectively; the chemical structure of the silicone-fluorine modified sulfonic acid photocurable resin is as follows:
[0009] .
[0010] Preferably, the trifunctional acrylate monomer is composed of ethoxylated trimethylolpropane triacrylate and propoxylated glycerol triacrylate in a mass ratio of 3:2 to 5:3.
[0011] Preferably, the difunctional acrylate monomer is tripropylene glycol diacrylate.
[0012] Preferably, the monofunctional acrylate monomer is composed of tetrahydrofurfuryl acrylate and isobornyl acrylate in a mass ratio of 1:2 to 1:3.
[0013] Preferably, the photoinitiator is composed of 1-hydroxycyclohexylphenyl ketone and 2,4,6-trimethylbenzoyl-diphenylphosphine oxide in a mass ratio of 2:1.
[0014] Preferably, the silicone-fluorine modified sulfonic acid photocurable resin is prepared by a method comprising the following steps:
[0015] (1) Glycidyl methacrylate was reacted with β-carboxyethyl acrylate to obtain a diacrylate hydroxy compound intermediate;
[0016] (2) 3-hydroxypropanesulfonic acid is reacted with phosphorus oxychloride to obtain a phosphoryl chloride intermediate containing a sulfonic acid group; then the phosphoryl chloride intermediate containing a sulfonic acid group is reacted with the diacrylate hydroxy compound intermediate obtained in step (1) to obtain a diacrylate phosphoryl chloride intermediate.
[0017] (3) The diacrylate phosphoryl chloride intermediate was reacted with 1,3-bis(4-hydroxybutyl)-1,1,3,3-tetramethyldisiloxane to obtain the diacrylate siloxane monohydroxy intermediate; the diacrylate phosphoryl chloride intermediate was reacted with 1H,1H,8H,8H-octafluoro-3,6-diox-1,8-octanediol to obtain the diacrylate fluoroether monohydroxy intermediate.
[0018] (4) React isophorone diisocyanate with 1,3,5-trihydroxyadamantane to obtain a terminal isocyanate compound; then react the terminal isocyanate compound with the diacrylate siloxane monohydroxy intermediate and then with the diacrylate fluoroether monohydroxy intermediate to obtain a silicone-fluorine modified sulfonic acid type photocurable resin.
[0019] Preferably, the molar ratio of glycidyl methacrylate to β-carboxyethyl acrylate is 1:1; and the molar ratio of 3-hydroxypropanesulfonic acid, the diacrylate hydroxy compound intermediate, and phosphorus oxychloride is 1:1:1.
[0020] Preferably, the molar ratio of the diacrylate phosphoryl chloride intermediate to 1,3-bis(4-hydroxybutyl)-1,1,3,3-tetramethyldisiloxane is 1:1; and the molar ratio of the diacrylate phosphoryl chloride intermediate to 1H,1H,8H,8H-octafluoro-3,6-diox-1,8-octanediol is 1:1.
[0021] Preferably, the molar ratio of isophorone diisocyanate, 1,3,5-trihydroxyadamantane, diacrylate siloxane monohydroxy intermediate and diacrylate fluoroether monohydroxy intermediate is 0.09:0.03:0.03:(0.06~0.065).
[0022] A method for preparing a topcoat for a photocurable diamond Mars coating as described above includes the following steps: mixing a silicone-fluorine modified sulfonic acid photocurable resin, a trifunctional acrylate monomer, a difunctional acrylate monomer, a monofunctional acrylate monomer, an ultra-hard wear-resistant powder, and a photoinitiator in a specified ratio to obtain a topcoat for a photocurable diamond Mars coating.
[0023] Compared with existing technologies, the beneficial effects of the photocurable diamond Martian coating topcoat and its preparation method of the present invention are as follows:
[0024] (1) The topcoat for the light-curing diamond Mars coating provided by the present invention uses a silicon-fluorine modified sulfonic acid type light-curing resin with adamantane as the core skeleton and containing sulfonic acid groups, organosilicon segments and organofluorine segments in its molecular structure as the matrix resin. The rigid cage structure of adamantane gives the resin high hardness and good thermal stability; the sulfonic acid groups can generate strong polar interactions with the surface of the superhard wear-resistant powder, enhancing the anchoring force of the filler; the silicon-oxygen bonds in the organosilicon segments have high bond energy and flexibility, which can form effective molecular chain entanglement and polar interaction at the interface between the coating and the primer layer, improving the wettability and adhesion anchoring force of the coating to the primer layer, while adjusting the flexibility and cross-linking density of the resin network, which helps to absorb and disperse external force impacts and reduce the tendency of wear-resistant powder particles to de-adhere under stress; the organofluorine segments, due to the low polarization rate and surface free energy of the carbon-fluorine bonds, can preferentially migrate to the coating surface and internal micropore interface during the curing process, forming a dense low surface energy barrier, effectively blocking the penetration and swelling damage of organic solvent molecules, and giving the coating excellent solvent resistance.
[0025] (2) This invention uses a compound of three superhard particles—diamond, zirconium oxide, and silicon carbide—as the superhard wear-resistant powder. Diamond, as the hardest known substance in nature, provides core scratch resistance; zirconium oxide, with its high fracture toughness, plays a buffering and auxiliary wear-resistant role during wear; and silicon carbide further fills microscopic gaps and increases the tortuosity of the wear path. The three work together to construct the superhard wear-resistant skeleton of the coating. At the same time, diamond, zirconium oxide, and silicon carbide have good interfacial wetting and affinity matching with the silicon-fluorine modified sulfonic acid type photocurable resin, realizing efficient anchoring of the superhard powder, effectively improving the anti-detachment performance of filler particles in the coating, and providing a good foundation for the long-term use of the topcoat coating.
[0026] (3) This invention utilizes a combination of trifunctional acrylate monomers (ethoxylated trimethylolpropane triacrylate and propoxylated glycerol triacrylate) and monofunctional acrylate monomers (tetrahydrofurfuryl acrylate and isobornyl acrylate) to effectively control the density and flexibility of the coating crosslinking network. The multifunctional monomers provide high crosslinking density and surface hardness, while the monofunctional monomers enhance the coating cohesion by adjusting the curing shrinkage rate through the polar anchoring effect of tetrahydrofurfuryl and the rigid cyclic structure of isobornyl. Attached Figure Description
[0027] Figure 1 The above is the 1H NMR spectrum of the diacrylate hydroxyl compound intermediate prepared in Example 1 of this invention;
[0028] Figure 2 The 1H NMR spectrum of the diacrylate phosphoryl chloride intermediate prepared in Example 1 of this invention;
[0029] Figure 3 The above is the 1H NMR spectrum of the diacrylate siloxane monohydroxy intermediate prepared in Example 1 of this invention;
[0030] Figure 4 The above is the 1H NMR spectrum of the diacrylate fluoroether monohydroxy intermediate prepared in Example 1 of this invention;
[0031] Figure 5 The 1H NMR spectrum of the silicone-fluorine modified sulfonic acid photocurable resin prepared in Example 1 of this invention;
[0032] Figure 6 The image shows the diamond Martian coating of Example 1 before the abrasion resistance test.
[0033] Figure 7 This is an image of the diamond Martian coating of Example 1 after a wear resistance test. Detailed Implementation
[0034] To enable those skilled in the art to better understand the technical solution, the present invention will be described in detail below with reference to embodiments. The description in this part is only exemplary and explanatory, and should not be used to limit the scope of protection of the present invention in any way.
[0035] Example 1
[0036] The topcoat for the photocurable diamond Mars coating of this embodiment is composed of the following components in parts by weight: 50 parts of silicone-fluorine modified sulfonic acid photocurable resin, 16 parts of trifunctional acrylate monomer, 10 parts of difunctional acrylate monomer, 4 parts of monofunctional acrylate monomer, 12 parts of superhard wear-resistant powder, and 4 parts of photoinitiator; the trifunctional acrylate monomer is composed of ethoxylated trimethylolpropane triacrylate and propoxylated glycerol triacrylate in a mass ratio of 3:2; the difunctional acrylate monomer is tripropylene glycol. Diacrylate; the monofunctional acrylate monomer is composed of tetrahydrofurfuryl acrylate and isobornyl acrylate in a mass ratio of 1:2; the superhard wear-resistant powder is composed of diamond particles, zirconium oxide particles and silicon carbide particles in a mass ratio of 4:7:9, with average particle sizes of 4μm, 14μm and 14μm for diamond particles, zirconium oxide particles and silicon carbide particles, respectively; the photoinitiator is a mixture of 1-hydroxycyclohexylphenyl ketone and 2,4,6-trimethylbenzoyl-diphenylphosphine oxide in a mass ratio of 2:1.
[0037] The preparation method of silicone-fluorine modified sulfonic acid type photocurable resin is as follows:
[0038] (1) Under nitrogen protection, 1.0 mol of glycidyl methacrylate, 1.0 mol of β-carboxyethyl acrylate, and 0.15 g of p-hydroxyanisole were added to a dry reaction flask equipped with a mechanical stirrer, thermometer, and reflux condenser. Stirring was started, nitrogen was introduced for 15 min, and the temperature was raised to 85 °C. Then, 2.5 g of triphenylphosphine was added, and the reaction was continued under nitrogen protection at 85 °C with stirring for 7 h. After the reaction was completed, the reaction solution was cooled to 60 °C and distilled under reduced pressure to constant weight under vacuum conditions ≤ -0.095 MPa to obtain the diacrylate hydroxyl compound intermediate. The 1H NMR spectrum of the diacrylate hydroxyl compound intermediate is shown below. Figure 1 As shown, the chemical structure is as follows:
[0039] .
[0040] (2) Under nitrogen protection, add 1.2 mol of phosphorus oxychloride and 600 mL of dichloromethane to a dry reaction flask equipped with a mechanical stirrer, thermometer and constant pressure dropping funnel. Turn on the stirrer and cool down to 0°C. Dissolve 1.0 mol of 3-hydroxypropanesulfonic acid in 300 mL of anhydrous tetrahydrofuran and add it dropwise to the reaction flask. Control the dropping rate so that the temperature of the reaction solution does not exceed 5°C. After the addition is complete, continue stirring at 0°C for 3 h. After the reaction is complete, remove the solvent and unreacted phosphorus oxychloride under reduced pressure at 45°C to obtain the intermediate 3-sulfonic acid propyl phosphate diacyl chloride.
[0041] The intermediate 3-sulfonyl propyl phosphate diacyl chloride, 400 mL of anhydrous dichloromethane, and 100 mL of anhydrous tetrahydrofuran were added to a reaction flask. After stirring until homogeneous, the mixture was cooled to 0°C. 1.0 mol of the diacrylate hydroxyl compound intermediate and 2.2 mol of the acid-binding agent triethylamine were dissolved in 180 mL of anhydrous dichloromethane and then added dropwise to the reaction solution. The dropping rate was controlled, and the reaction temperature was maintained between 0 and 5°C. After the addition was complete, the mixture was stirred at 0°C for 6 hours. After the reaction was completed, the mixture was filtered under nitrogen protection while cold. The filtrate was then concentrated by vacuum distillation at 35°C. One-third of the volume was used to obtain a concentrated solution. Under stirring, the concentrated solution was added dropwise to 500 mL of anhydrous petroleum ether. After the addition was complete, the solution was cooled to 0°C in an ice-water bath, stirred for 15 min, and allowed to stand for 2 h. The lower viscous phase was separated, and the upper petroleum ether supernatant was discarded. 20 mL of dichloromethane was added to the lower viscous phase, and after thorough stirring, 100 mL of anhydrous petroleum ether was added. After stirring and standing, the lower viscous phase was separated. The lower viscous phase was concentrated to constant weight under reduced pressure at 35°C and a vacuum degree ≤-0.095 MPa under nitrogen protection to obtain the diacrylate phosphoryl chloride intermediate. The 1H NMR spectrum of the diacrylate phosphoryl chloride intermediate is shown below. Figure 2 As shown, the chemical structure is as follows:
[0042] .
[0043] (3) Under nitrogen protection, 0.06 mol of 1,3-bis(4-hydroxybutyl)-1,1,3,3-tetramethyldisiloxane, 80 mL of anhydrous tetrahydrofuran, and 0.1 mol of triethylamine were added to a dry reaction flask. The temperature was lowered to 0°C. 0.06 mol of the diacrylate phosphoryl chloride intermediate was dissolved in 40 mL of anhydrous tetrahydrofuran and then added dropwise to the reaction flask. The dropping rate was controlled to maintain the material temperature at 0~5°C. After the addition was complete, the temperature was naturally raised to room temperature, and the reaction was stirred for 6 h. After the reaction was completed, the mixture was filtered to remove the generated triethylamine hydrochloride. The filtrate was concentrated under reduced pressure to constant weight at 40°C and a vacuum degree ≤-0.095 MPa to obtain the diacrylate siloxane monohydroxy intermediate. The chemical structure of 1,3-bis(4-hydroxybutyl)-1,1,3,3-tetramethyldisiloxane is as follows:
[0044] ;
[0045] The 1H NMR spectrum of the diacrylate siloxane monohydroxy intermediate is shown below. Figure 3 As shown, the chemical structure is as follows:
[0046] .
[0047] Under nitrogen protection, 0.06 mol of 1H,1H,8H,8H-octafluoro-3,6-diox-1,8-octanediol, 100 mL of anhydrous tetrahydrofuran, and 0.1 mol of triethylamine were added to a dry reaction flask. The mixture was cooled to 0°C. 0.06 mol of the diacrylate phosphoryl chloride intermediate was dissolved in 40 mL of anhydrous tetrahydrofuran and added dropwise to the reaction flask. The dropping rate was controlled to maintain the material temperature between 0 and 5°C. After the addition was complete, the mixture was allowed to warm naturally to room temperature, and the reaction was continued with stirring for 6 hours. After the reaction was complete, the mixture was filtered to remove the generated triethylamine hydrochloride. The filtrate was concentrated under reduced pressure to constant weight at 40°C and a vacuum degree ≤ -0.095 MPa to obtain the diacrylate fluoroether monohydroxy intermediate. The chemical structure of 1H,1H,8H,8H-octafluoro-3,6-diox-1,8-octanediol is as follows:
[0048] ;
[0049] The 1H NMR spectrum of the diacrylate fluoroether monohydroxy intermediate is shown below. Figure 4 As shown, the chemical structure is as follows:
[0050] .
[0051] (4) Under nitrogen protection, add 0.09 mol of isophorone diisocyanate and 80 mL of anhydrous tetrahydrofuran to a dry flask equipped with a mechanical stirrer, thermometer, and constant pressure dropping funnel. Start stirring and cool to 0°C in an ice-water bath. Dissolve 0.03 mol of 1,3,5-trihydroxyadamantane in 120 mL of anhydrous tetrahydrofuran and add it dropwise to the reaction flask. Control the dropping rate to keep the temperature of the reaction solution below 10°C. After the addition is complete, add 0.18 mmol of dibutyltin dilaurate as a catalyst. Stir evenly and then heat to 45°C. Maintain the temperature and stir for 6 h. After the reaction is complete, cool to room temperature to obtain a tetrahydrofuran solution of the isocyanate-terminated compound. The chemical structure of 1,3,5-trihydroxyadamantane is as follows:
[0052] .
[0053] A tetrahydrofuran solution of the isocyanate-terminated compound was added to the reaction flask. Then, 0.05 mmol of dibutyltin dilaurate was added, and the temperature of the mixture in the reaction flask was adjusted to 30°C. 0.03 mol of a diacrylate siloxane monohydroxy intermediate was dissolved in 60 mL of anhydrous tetrahydrofuran and added dropwise to the reaction flask, maintaining the temperature at 30–35°C. After the addition was complete, the mixture was stirred and kept at 30°C for 4 hours. Finally, 0.065 mol of a diacrylate fluoroether monohydroxy intermediate was dissolved in 70 mL of anhydrous tetrahydrofuran and added dropwise to the reaction flask. The temperature was raised to 55℃, and the reaction was maintained at this temperature with stirring for 6 hours. After the reaction was completed, the temperature was lowered to room temperature, and the insoluble matter was removed by filtration. The filtrate was concentrated under reduced pressure at 40℃ to 1 / 5 of its original volume to obtain a concentrate. 50 mL of anhydrous tetrahydrofuran was added to the concentrate, and after stirring evenly, it was added dropwise to 500 mL of anhydrous petroleum ether. After the addition was complete, the mixture was placed in an ice-water bath and cooled to 0℃. After standing for 1 hour, the lower viscous phase was separated, and the upper clear liquid was discarded. The lower viscous phase was washed twice with anhydrous petroleum ether (50 mL × 2). Finally, it was dried under vacuum at 50℃ to constant weight to obtain the silicone-fluorine modified sulfonic acid type photocurable resin. The 1H NMR spectrum of the silicone-fluorine modified sulfonic acid type photocurable resin is shown below. Figure 5 As shown, the chemical structure is as follows:
[0054] .
[0055] Example 2
[0056] The topcoat for the photocurable diamond Mars coating of this embodiment is composed of the following components in parts by weight: 55 parts of silicone-fluorine modified sulfonic acid photocurable resin, 15 parts of trifunctional acrylate monomer, 8 parts of difunctional acrylate monomer, 5 parts of monofunctional acrylate monomer, 14 parts of superhard wear-resistant powder, and 4.5 parts of photoinitiator; the trifunctional acrylate monomer is composed of ethoxylated trimethylolpropane triacrylate and propoxylated glycerol triacrylate in a mass ratio of 4:3; the difunctional acrylate monomer is tripropylene glycol. Diacrylate; the monofunctional acrylate monomer is composed of tetrahydrofurfuryl acrylate and isobornyl acrylate in a mass ratio of 1:2; the superhard wear-resistant powder is composed of diamond particles, zirconium oxide particles and silicon carbide particles in a mass ratio of 4:8:10, with average particle sizes of 5 μm, 14 μm and 14 μm for the diamond particles, zirconium oxide particles and silicon carbide particles, respectively; the photoinitiator is a mixture of 1-hydroxycyclohexylphenyl ketone and 2,4,6-trimethylbenzoyl-diphenylphosphine oxide in a mass ratio of 2:1. The silicone-fluorine modified sulfonic acid type photocurable resin in this example is the same as the silicone-fluorine modified sulfonic acid type photocurable resin in Example 1.
[0057] Example 3
[0058] The topcoat for the photocurable diamond Mars coating of this embodiment is composed of the following components in parts by weight: 60 parts of silicone-fluorine modified sulfonic acid photocurable resin, 11 parts of trifunctional acrylate monomer, 12 parts of difunctional acrylate monomer, 3 parts of monofunctional acrylate monomer, 16 parts of superhard wear-resistant powder, and 5 parts of photoinitiator; the trifunctional acrylate monomer is composed of ethoxylated trimethylolpropane triacrylate and propoxylated glycerol triacrylate in a mass ratio of 5:3; the difunctional acrylate monomer is tripropylene glycol diacetate. The acrylate monomers consist of tetrahydrofurfuryl acrylate and isobornyl acrylate in a mass ratio of 1:3; the superhard wear-resistant powder consists of diamond particles, zirconium oxide particles, and silicon carbide particles in a mass ratio of 5:9:12, with average particle sizes of 6 μm, 16 μm, and 16 μm, respectively; the photoinitiator is a mixture of 1-hydroxycyclohexylphenyl ketone and 2,4,6-trimethylbenzoyl-diphenylphosphine oxide in a mass ratio of 2:1. The silicone-fluorine modified sulfonic acid type photocurable resin in this example is the same as the silicone-fluorine modified sulfonic acid type photocurable resin in Example 1.
[0059] The preparation method of the topcoat for the photocurable diamond Mars coating in Examples 1-3 includes the following steps: adding trifunctional acrylate monomers, difunctional acrylate monomers and monofunctional acrylate monomers to a dispersion tank, stirring and mixing evenly, then adding silicone-fluorine modified sulfonic acid type photocurable resin, stirring until completely dissolved, then adding superhard wear-resistant powder, stirring and dispersing evenly, and finally adding photoinitiator, stirring until the photoinitiator is completely dissolved to obtain the topcoat for the photocurable diamond Mars coating.
[0060] Comparative Example 1
[0061] The only difference between the photocurable diamond Mars coating topcoat of this comparative example and the photocurable diamond Mars coating topcoat of Example 1 is that the amount of diamond particles in the superhard wear-resistant powder of this comparative example is 0, and the mass ratio of zirconium oxide particles to silicon carbide particles is 7:9.
[0062] Comparative Example 2
[0063] The only difference between the photocurable diamond Mars coating topcoat of this comparative example and the photocurable diamond Mars coating topcoat of Example 1 is that the amount of zirconium oxide particles in the superhard wear-resistant powder of this comparative example is 0, and the mass ratio of diamond particles to silicon carbide particles is 4:9.
[0064] Comparative Example 3
[0065] The only difference between the photocurable diamond Mars coating topcoat of this comparative example and the photocurable diamond Mars coating topcoat of Example 1 is that the amount of silicon carbide particles in the superhard wear-resistant powder of this comparative example is 0, and the mass ratio of diamond particles to zirconium oxide particles is 4:7.
[0066] Comparative Example 4
[0067] The only difference between the photocurable diamond Mars coating topcoat of this comparative example and the photocurable diamond Mars coating topcoat of Example 1 is that the zirconium oxide particles in the ultra-hard wear-resistant powder of this comparative example are replaced with aluminum oxide particles of the same particle size.
[0068] Comparative Example 5
[0069] The only difference between the photocurable diamond Mars coating topcoat of this comparative example and the photocurable diamond Mars coating topcoat of Example 1 is that the silicon carbide particles in the ultra-hard wear-resistant powder of this comparative example are replaced with boron carbide particles of the same particle size.
[0070] Comparative Example 6
[0071] The only difference between the photocurable diamond Mars coating topcoat of this comparative example and the photocurable diamond Mars coating topcoat of Example 1 is that the silicone-fluorine modified sulfonic acid type photocurable resin is replaced with a silicone modified sulfonic acid type photocurable resin in the photocurable diamond Mars coating topcoat of this comparative example. The preparation method of the silicone modified sulfonic acid type photocurable resin is as follows:
[0072] (1) This step is the same as step (1) of the preparation method of the silicone-fluorine modified sulfonic acid type photocurable resin in the photocurable diamond Martian coating topcoat of Example 1;
[0073] (2) This step is the same as step (2) of the preparation method of the silicone-fluorine modified sulfonic acid type photocurable resin in the photocurable diamond Martian coating topcoat of Example 1;
[0074] (3) This step is the same as step (3) of the preparation method of the silicone-fluorine modified sulfonic acid type photocurable resin in the photocurable diamond Martian coating topcoat of Example 1;
[0075] (4) Under nitrogen protection, add 0.09 mol of isophorone diisocyanate and 80 mL of anhydrous tetrahydrofuran to a dry flask equipped with a mechanical stirrer, thermometer and constant pressure dropping funnel. Start stirring and cool to 0°C in an ice-water bath. Dissolve 0.03 mol of 1,3,5-trihydroxyadamantane in 120 mL of anhydrous tetrahydrofuran and add it dropwise to the reaction flask. Control the dropping rate so that the temperature of the reaction solution does not exceed 10°C. After the addition is complete, add 0.18 mmol of dibutyltin dilaurate as a catalyst. Stir evenly and heat to 45°C. Keep the temperature and stir for 6 h. After the reaction is complete, cool to room temperature to obtain a tetrahydrofuran solution of the isocyanate-terminated compound.
[0076] A tetrahydrofuran solution of the isocyanate-terminated compound was added to the reaction flask, followed by 0.05 mmol of dibutyltin dilaurate. The temperature of the mixture in the reaction flask was adjusted to 30°C. 0.095 mol of a diacrylate siloxane monohydroxy intermediate was dissolved in 130 mL of anhydrous tetrahydrofuran and then added dropwise to the reaction flask, maintaining the temperature at 30–35°C. After the addition was complete, the mixture was kept at 30°C with stirring for 4 hours. The temperature was then increased to 55°C and the mixture was kept at this temperature with stirring for 6 hours until the reaction was complete. The solution was then cooled to room temperature, filtered to remove insoluble matter, and concentrated under reduced pressure at 40°C to 1 / 5 of its original volume to obtain a concentrate. 50 mL of anhydrous tetrahydrofuran was added to the concentrate, and after stirring thoroughly, it was added dropwise to 500 mL of anhydrous petroleum ether. After the addition was complete, the solution was cooled to 0°C in an ice-water bath and allowed to stand for 1 hour. The lower viscous phase was separated, and the upper clear liquid was discarded. The lower viscous phase was washed twice with anhydrous petroleum ether (50 mL × 2). Finally, it was vacuum dried at 50°C to constant weight to obtain the silicone-modified sulfonic acid type photocurable resin. The chemical structure of the silicone-modified sulfonic acid type photocurable resin is as follows:
[0077] .
[0078] Comparative Example 7
[0079] The only difference between the photocurable diamond Mars coating topcoat of this comparative example and the photocurable diamond Mars coating topcoat of Example 1 is that the silicone-fluorine modified sulfonic acid photocurable resin is replaced with fluorine modified sulfonic acid photocurable resin in the photocurable diamond Mars coating topcoat of this comparative example. The preparation method of the fluorine modified sulfonic acid photocurable resin is as follows:
[0080] (1) This step is the same as step (1) of the preparation method of the silicone-fluorine modified sulfonic acid type photocurable resin in the photocurable diamond Martian coating topcoat of Example 1;
[0081] (2) This step is the same as step (2) of the preparation method of the silicone-fluorine modified sulfonic acid type photocurable resin in the photocurable diamond Martian coating topcoat of Example 1;
[0082] (3) This step is the same as step (3) of the preparation method of the silicone-fluorine modified sulfonic acid type photocurable resin in the photocurable diamond Martian coating topcoat of Example 1;
[0083] (4) Under nitrogen protection, add 0.09 mol of isophorone diisocyanate and 80 mL of anhydrous tetrahydrofuran to a dry flask equipped with a mechanical stirrer, thermometer and constant pressure dropping funnel. Start stirring and cool to 0°C in an ice-water bath. Dissolve 0.03 mol of 1,3,5-trihydroxyadamantane in 120 mL of anhydrous tetrahydrofuran and add it dropwise to the reaction flask. Control the dropping rate so that the temperature of the reaction solution does not exceed 10°C. After the addition is complete, add 0.18 mmol of dibutyltin dilaurate as a catalyst. Stir evenly and heat to 45°C. Keep the temperature and stir for 6 h. After the reaction is complete, cool to room temperature to obtain a tetrahydrofuran solution of the isocyanate-terminated compound.
[0084] A tetrahydrofuran solution of the isocyanate-terminated compound was added to the reaction flask, followed by 0.05 mmol of dibutyltin dilaurate. The temperature of the mixture in the reaction flask was adjusted to 30°C. 0.095 mol of a diacrylate fluoroether monohydroxy intermediate was dissolved in 130 mL of anhydrous tetrahydrofuran and added dropwise to the reaction flask, maintaining the temperature at 30–35°C. After the addition was complete, the mixture was kept at 30°C with stirring for 4 hours. The temperature was then increased to 55°C and the mixture was kept at this temperature with stirring for 6 hours. After the reaction was complete, the mixture was cooled to room temperature. The insoluble matter was removed by filtration. The filtrate was concentrated under reduced pressure at 40°C to 1 / 5 of its original volume to obtain a concentrate. 50 mL of 1,1,1,3,3,3-hexafluoroisopropanol was added to the concentrate, and after stirring thoroughly, it was added dropwise to 500 mL of anhydrous n-hexane. After the addition was complete, the mixture was cooled to 0°C in an ice-water bath and allowed to stand for 1 hour. The lower viscous phase was separated, and the upper clear liquid was discarded. The lower viscous phase was washed twice with anhydrous n-hexane (50 mL × 2). Finally, it was vacuum dried at 50°C to constant weight to obtain the fluorinated sulfonic acid type photocurable resin. The chemical structure of the fluorinated sulfonic acid type photocurable resin is as follows:
[0085] .
[0086] Comparative Example 8
[0087] The only difference between the UV-curable diamond Mars coating topcoat of this comparative example and the UV-curable diamond Mars coating topcoat of Example 1 is that the preparation method of the silicone-fluorine modified sulfonic acid type UV-curable resin in the UV-curable diamond Mars coating topcoat of this comparative example is as follows: the silicone-modified sulfonic acid type UV-curable resin in the UV-curable diamond Mars coating topcoat of Comparative Example 6 and the fluorine-modified sulfonic acid type UV-curable resin in the UV-curable diamond Mars coating topcoat of Comparative Example 7 are stirred and mixed evenly at a mass ratio of 1:1 to obtain the final product.
[0088] Comparative Example 9
[0089] The only difference between the photocurable diamond Mars coating topcoat of this comparative example and the photocurable diamond Mars coating topcoat of Example 1 is that the preparation method of the silicone-fluorine modified sulfonic acid type photocurable resin in the photocurable diamond Mars coating topcoat of this comparative example is as follows:
[0090] (1) This step is the same as step (1) of the preparation method of the silicone-fluorine modified sulfonic acid type photocurable resin in the photocurable diamond Martian coating topcoat of Example 1;
[0091] (2) This step is the same as step (2) of the preparation method of the silicone-fluorine modified sulfonic acid type photocurable resin in the photocurable diamond Martian coating topcoat of Example 1;
[0092] (3) This step is the same as step (3) of the preparation method of the silicone-fluorine modified sulfonic acid type photocurable resin in the photocurable diamond Martian coating topcoat of Example 1;
[0093] (4) Under nitrogen protection, add 0.09 mol of isophorone diisocyanate and 80 mL of anhydrous tetrahydrofuran to a dry flask equipped with a mechanical stirrer, thermometer and constant pressure dropping funnel. Start stirring and cool to 0°C in an ice-water bath. Dissolve 0.03 mol of 1,3,5-trihydroxyadamantane in 120 mL of anhydrous tetrahydrofuran and add it dropwise to the reaction flask. Control the dropping rate so that the temperature of the reaction solution does not exceed 10°C. After the addition is complete, add 0.18 mmol of dibutyltin dilaurate as a catalyst. Stir evenly and heat to 45°C. Keep the temperature and stir for 6 h. After the reaction is complete, cool to room temperature to obtain a tetrahydrofuran solution of the isocyanate-terminated compound.
[0094] A tetrahydrofuran solution of the isocyanate-terminated compound was added to the reaction flask. Then, 0.05 mmol of dibutyltin dilaurate was added, and the temperature of the mixture in the reaction flask was adjusted to 30°C. 0.06 mol of a diacrylate siloxane monohydroxy intermediate was dissolved in 90 mL of anhydrous tetrahydrofuran and added dropwise to the reaction flask, maintaining the temperature at 30–35°C. After the addition was complete, the mixture was stirred and kept at 30°C for 6 hours. Finally, 0.035 mol of a diacrylate fluoroether monohydroxy intermediate was dissolved in 40 mL of anhydrous tetrahydrofuran and added dropwise to the reaction flask. The temperature was raised to 55℃, and the reaction was maintained at this temperature with stirring for 5 hours. After the reaction was completed, the temperature was lowered to room temperature, and the insoluble matter was removed by filtration. The filtrate was concentrated under reduced pressure at 40℃ to 1 / 5 of its original volume to obtain a concentrate. 50 mL of anhydrous tetrahydrofuran was added to the concentrate, and after stirring evenly, it was added dropwise to 500 mL of anhydrous petroleum ether. After the addition was complete, the mixture was placed in an ice-water bath and cooled to 0℃. After standing for 1 hour, the lower viscous phase was separated, and the upper clear liquid was discarded. The lower viscous phase was washed twice with anhydrous petroleum ether (50 mL × 2). Finally, it was vacuum dried at 50℃ to constant weight to obtain the silicone-fluorine modified sulfonic acid type photocurable resin. The chemical structure of the silicone-fluorine modified sulfonic acid type photocurable resin is as follows:
[0095] .
[0096] Experimental Example
[0097] To examine the comprehensive performance of the topcoat for the photocurable diamond Mars coating in each embodiment and comparative example, coatings for the photocurable diamond Mars coating in each embodiment and comparative example were prepared using the following methods: For high-density fiberboard (HDF, density ≥ 0.85 g / cm³), the topcoat was applied to... 3 The surface of the high-density fiberboard is sanded with 240 grit, and then coated (brushed) with a UV-cured diamond Mars coating primer at a coverage of 65 g / m². 2 After coating, the product is dried using a UV curing lamp with a UV energy of 150 mJ / cm². 2The primer is cured by UV to form a base coat; then the topcoat is applied (brushed) onto the primer coat, with a coverage of 30g / m². 2 After coating, the material is dried using a UV curing lamp with a UV energy of 500 mJ / cm². 2 After UV curing, the topcoat layer is formed and cured at 25℃ for 12 hours before testing for adhesion, hardness, abrasion resistance, and solvent resistance. To test the adhesion of the superhard abrasion-resistant powder, the tinplate surface is sanded with a 240-grit finish, and then the topcoat is applied (brushed) to the sanded tinplate surface at a coverage of 30 g / m². 2 After coating, the material is dried using a UV curing lamp with a UV energy of 500 mJ / cm². 2 After UV curing, the topcoat layer is formed. After curing at 25℃ for 12 hours, the adhesion strength of the superhard wear-resistant powder is tested.
[0098] The adhesion test was conducted according to the requirements of standard GB / T 5210-2006. A 20mm diameter test column was adhered to the cured coating surface. After curing, a tensile force was applied perpendicular to the board surface until the coating was pulled off, and the maximum tensile force at failure was recorded. The hardness test was conducted according to the requirements of standard GB / T 6739-2006. The abrasion resistance test was conducted according to the requirements of standard GB / T 1768-2006. A Taber abrasion tester was used with a loading pressure of 5N. The diamond Martian coating was rotated and rubbed with P180 grit (180 mesh) abrasive cloth. The abrasive paper was replaced every 500 revolutions to avoid abrasion and test deviation. During the test, the coating was divided into four equal parts. The test was stopped when three parts showed a 95% exposure rate (the exposure rate is defined as the proportion of the area of the underlying substrate exposed when the coating surface is worn through to the total test area). The corresponding number of rotations was recorded as the abrasion resistance test result. Solvent resistance was tested according to standard GB / T The acetone wiping test specified in GB / T 23989-2009 involves smearing a cotton swab with acetone and applying a force of 1N to the coating surface, wiping back and forth at a rate of 60 swipes per minute until the primer is clearly exposed (film breakage). The number of swipes is recorded as the solvent resistance test result. The test method for the adhesion strength of the superhard abrasion-resistant powder is as follows: the cured coating sample (substrate is tinplate) is cut into 10cm × 10cm pieces with an accuracy of 0.01m. The initial mass m1 of the topcoat coating on the test specimen was weighed using an analytical balance (calculated by the mass difference between the specimen before and after coating). The specimen was placed coating-side down on the pad of the impact testing machine, and a 1kg hammer was dropped to impact the back of the specimen, subjecting the coating surface to instantaneous tension. After the impact, the debris loosened by the impact was gently brushed away with a soft brush, and the specimen was weighed again to calculate the remaining mass m2 of the topcoat coating. The impact dust removal rate was calculated as (m1-m2) / m1×100%. The lower the dust removal rate, the stronger the interfacial anchorage of the ultra-hard powder in the coating. The test conditions were the same for all samples, and each sample was tested 3 times. The average value was calculated after the test.
[0099] Table 1 shows the test results of adhesion, hardness, abrasion resistance, solvent resistance, and adhesion strength of the superhard abrasion-resistant powder to the topcoat used for diamond Mars coatings in each embodiment and comparative example. Images of the diamond Mars coating prepared with the photocurable diamond Mars coating topcoat of Example 1 before and after the abrasion resistance test are shown below. Figure 6 and Figure 7 As shown.
[0100] Table 1. Comprehensive performance test results of diamond Martian coatings prepared with topcoat for UV-cured diamond Martian coating.
[0101]
[0102] As can be seen from the test results in Table 1, the topcoat for the light-cured diamond Mars coating provided by the present invention has good adhesion, hardness, abrasion resistance, solvent resistance and low impact powdering rate, showing good comprehensive performance.
[0103] Comparing the test results of Example 1 with those of Comparative Examples 1-3, it can be seen that when diamond particles, zirconium oxide particles, or silicon carbide particles are missing from the superhard wear-resistant powder, the adhesion, hardness, wear resistance, and solvent resistance of the coating all decrease to varying degrees, and the impact powdering rate increases. This indicates that diamond, zirconium oxide, and silicon carbide particles do not play an isolated role in the coating system. Diamond acts as the core wear-resistant phase with ultra-high hardness, zirconium oxide plays a buffering and auxiliary wear-resistant role due to its high fracture toughness, and silicon carbide may play a role by filling microscopic gaps and increasing the tortuosity of the wear path. Together, the three constitute the basic framework for maintaining the coating's ultrahard wear resistance and interface anchoring.
[0104] Comparing the test results of Example 1 and Comparative Examples 4-5, it can be seen that when zirconium oxide particles are replaced with alumina particles of the same size, or silicon carbide particles are replaced with boron carbide particles of the same size, the hardness of the coating is retained to some extent, but the impact powdering rate increases, and the adhesion and solvent resistance also deteriorate. This indicates that, in addition to providing basic hardness, zirconium oxide and silicon carbide particles, more importantly, have better interfacial compatibility and chemical affinity with the silicone-fluorine modified sulfonic acid photocurable resin, enabling them to be well wetted and firmly anchored by the resin, thereby improving the overall performance of the coating. This may be because the difference in electronegativity of different elements determines the different polarities of the chemical bonds on the particle surface, thus affecting the resin's wetting and interfacial bonding force.
[0105] Comparing the test results of Example 1 and Comparative Examples 6-8, it can be seen that when only organosilicon segments are introduced into the resin and organofluorine segments are lacking, the solvent resistance of the coating deteriorates and the powdering rate increases; when only organofluorine segments are introduced and organosilicon segments are lacking, the adhesion of the coating deteriorates, the hardness decreases, and the powdering rate increases. The silicon-oxygen bonds in the organosilicon segments have high bond energy and flexibility, which can form effective molecular chain entanglement and polar interaction at the interface between the coating and the primer layer, thereby helping to improve the wettability and adhesion anchoring force of the coating to the substrate; at the same time, the introduction of organosilicon segments can adjust the flexibility and cross-linking density of the resin network, which helps to absorb and disperse external impacts and reduce the tendency of wear-resistant powder particles to de-adhede under stress. Organic fluorine segments, due to the low polarizability and surface free energy of carbon-fluorine bonds, preferentially migrate to the coating surface and internal micropore interface during curing, forming a dense, low surface energy barrier. This helps to block the penetration and swelling damage of solvent molecules such as acetone. Simultaneously, this surface enrichment effect also helps to enhance the density of the resin's coating on the wear-resistant powder particles. However, when only organic fluorine segments are present, their excessively low surface energy leads to insufficient spreading and penetration of the resin into the substrate, weakening interfacial adhesion and macroscopically manifesting as poor adhesion. When only organosilicon segments are present, the lack of a dense surface barrier from fluorine segments results in deteriorated solvent resistance. In Comparative Example 8, when the two were physically blended, the poor thermodynamic compatibility between the silicone and fluorine segment resins easily led to the formation of a micro-phase separation structure after curing, making it difficult to construct a continuous, uniform, and dense network. This resulted in interfacial stress concentration and solvent penetration channels, leading to poor overall performance.
[0106] Comparing the test results of Example 1 and Comparative Example 9, it can be seen that when the ratio of organosilicon segments to organofluorine segments in the resin is changed, the coating exhibits poor abrasion resistance and solvent resistance, and a high impact powdering rate. This result indicates that around the rigid crosslinked core constructed from isophorone diisocyanate and 1,3,5-trihydroxyadamantane, a suitable ratio of organosilicon to organofluorine side chains is necessary to achieve a good balance between the cohesive strength of the resin system, substrate wettability, and powder anchoring force.
[0107] In summary, the photocurable diamond Mars coating topcoat provided by the present invention is prepared by mixing a photocurable resin with adamantane as the core skeleton and containing sulfonic acid groups, organosilicon segments and organofluorine segments in its molecular structure with an ultra-hard wear-resistant powder composed of diamond particles, zirconium oxide particles and silicon carbide particles. It has high adhesion, hardness, good wear resistance, solvent resistance and filler anchoring force.
[0108] It should be noted that, in this document, the terms "comprising," "including," and any other variations are intended to cover non-exclusive inclusion, such that a process, method, article, or apparatus that comprises a list of elements includes not only those elements but also other elements not expressly listed, or elements inherent to such a process, method, article, or apparatus. Specific examples have been used in this document to illustrate the principles and implementation methods of the present invention. These examples are merely for the purpose of helping to understand the method and core ideas of the present invention. The above descriptions are only preferred embodiments of the present invention. It should be pointed out that, due to the limitations of written expression and the objective existence of infinite specific structures, those skilled in the art can make several improvements, modifications, or variations without departing from the principles of the present invention, and can also combine the above technical features in an appropriate manner. These improvements, modifications, variations, or combinations, or the direct application of the concept and technical solution of the present invention to other situations without modification, should all be considered within the scope of protection of the present invention.
Claims
1. A topcoat for a light-cured diamond Martian coating, characterized in that, The product is composed of the following components in parts by weight: 50-60 parts of silicone-fluorine modified sulfonic acid photocurable resin, 11-16 parts of trifunctional acrylate monomer, 8-12 parts of difunctional acrylate monomer, 3-5 parts of monofunctional acrylate monomer, 12-16 parts of superhard wear-resistant powder, and 4-5 parts of photoinitiator; the superhard wear-resistant powder is composed of diamond particles, zirconium oxide particles, and silicon carbide particles in a mass ratio of 4-5:7-9:9-12, with average particle sizes of 4-8 μm, 10-16 μm, and 10-16 μm, respectively; the chemical structure of the silicone-fluorine modified sulfonic acid photocurable resin is as follows: 。 2. The topcoat for photocurable diamond Martian coating according to claim 1, characterized in that, The trifunctional acrylate monomer is composed of ethoxylated trimethylolpropane triacrylate and propoxylated glycerol triacrylate in a mass ratio of 3:2 to 5:
3.
3. The topcoat for photocurable diamond Martian coating according to claim 1, characterized in that, The bifunctional acrylate monomer is tripropylene glycol diacrylate.
4. The topcoat for photocurable diamond Martian coating according to claim 1, characterized in that, The monofunctional acrylate monomer is composed of tetrahydrofurfuryl acrylate and isobornyl acrylate in a mass ratio of 1:2 to 1:
3.
5. The topcoat for photocuring diamond Martian coating according to claim 1, characterized in that, The photoinitiator is composed of 1-hydroxycyclohexylphenyl ketone and 2,4,6-trimethylbenzoyl-diphenylphosphine oxide in a mass ratio of 2:
1.
6. The topcoat for photocuring diamond Martian coating according to any one of claims 1-5, characterized in that, The silicone-fluorine modified sulfonic acid photocurable resin is prepared by a method comprising the following steps: (1) Glycidyl methacrylate was reacted with β-carboxyethyl acrylate to obtain a diacrylate hydroxy compound intermediate; (2) 3-hydroxypropanesulfonic acid is reacted with phosphorus oxychloride to obtain a phosphoryl chloride intermediate containing a sulfonic acid group; then the phosphoryl chloride intermediate containing a sulfonic acid group is reacted with the diacrylate hydroxy compound intermediate obtained in step (1) to obtain a diacrylate phosphoryl chloride intermediate. (3) The diacrylate phosphoryl chloride intermediate was reacted with 1,3-bis(4-hydroxybutyl)-1,1,3,3-tetramethyldisiloxane to obtain the diacrylate siloxane monohydroxy intermediate; the diacrylate phosphoryl chloride intermediate was reacted with 1H,1H,8H,8H-octafluoro-3,6-diox-1,8-octanediol to obtain the diacrylate fluoroether monohydroxy intermediate. (4) React isophorone diisocyanate with 1,3,5-trihydroxyadamantane to obtain a terminal isocyanate compound; then react the terminal isocyanate compound with the diacrylate siloxane monohydroxy intermediate and then with the diacrylate fluoroether monohydroxy intermediate to obtain a silicone-fluorine modified sulfonic acid type photocurable resin.
7. The topcoat for photocuring diamond Martian coating according to claim 6, characterized in that, The molar ratio of glycidyl methacrylate to β-carboxyethyl acrylate is 1:1; the molar ratio of 3-hydroxypropanesulfonic acid, diacrylate hydroxy compound intermediate, and phosphorus oxychloride is 1:1:
1.
8. The topcoat for photocuring diamond Martian coating according to claim 6, characterized in that, The molar ratio of the diacrylate phosphoryl chloride intermediate to 1,3-bis(4-hydroxybutyl)-1,1,3,3-tetramethyldisiloxane is 1:1; the molar ratio of the diacrylate phosphoryl chloride intermediate to 1H,1H,8H,8H-octafluoro-3,6-diox-1,8-octanediol is 1:
1.
9. The topcoat for photocuring diamond Martian coating according to claim 6, characterized in that, The molar ratio of isophorone diisocyanate, 1,3,5-trihydroxyadamantane, diacrylate siloxane monohydroxy intermediate and diacrylate fluoroether monohydroxy intermediate is 0.09:0.03:0.03:(0.06~0.065).
10. A method for preparing a topcoat for a light-cured diamond Martian coating as described in any one of claims 1-9, characterized in that, Includes the following steps: A photocurable topcoat for a diamond Martian coating is prepared by uniformly mixing a silicone-fluorine modified sulfonic acid type photocurable resin, a trifunctional acrylate monomer, a difunctional acrylate monomer, a monofunctional acrylate monomer, an ultra-hard wear-resistant powder, and a photoinitiator according to a specified ratio.
Citation Information
Patent Citations
Ultra-wear-resistant and high-temperature-resistant stone powder and PVC (polyvinyl chloride) material floor ultraviolet curing coating and preparation method thereof
CN116285650A